2014
DOI: 10.3389/fphys.2014.00064
|View full text |Cite
|
Sign up to set email alerts
|

Biosonar resolving power: echo-acoustic perception of surface structures in the submillimeter range

Abstract: The minimum distance for which two points still can be separated from each other defines the resolving power of a visual system. In an echo-acoustic context, the resolving power is usually measured as the smallest perceivable distance of two reflecting surfaces on the range axis and is found to be around half a millimeter for bats employing frequency modulated (FM) echolocation calls. Only few studies measured such thresholds with physical objects, most often bats were trained on virtual echoes i.e., echoes ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Schmidt showed that the bat Megaderma lyra is able to discriminate between two phantom targets producing echoes with a delay between them of about 1 µs [12] with waveforms of a bandwidth of up to 100 kHz, suggesting the bat capability to achieve higher range resolution performance with respect to the conventional matched filter (above 10 µs or 1.7 mm for speed of sound 340 m/s). Discrimination of surface structures is demonstrated in [13] where Glossophaga soricina were trained to distinguish smooth surface from coarse with a structure depth bigger than 0.38 mm. The emitted frequency modulated down-chirp had three harmonics -95-55 kHz, 150-86 kHz and 190-140 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…Schmidt showed that the bat Megaderma lyra is able to discriminate between two phantom targets producing echoes with a delay between them of about 1 µs [12] with waveforms of a bandwidth of up to 100 kHz, suggesting the bat capability to achieve higher range resolution performance with respect to the conventional matched filter (above 10 µs or 1.7 mm for speed of sound 340 m/s). Discrimination of surface structures is demonstrated in [13] where Glossophaga soricina were trained to distinguish smooth surface from coarse with a structure depth bigger than 0.38 mm. The emitted frequency modulated down-chirp had three harmonics -95-55 kHz, 150-86 kHz and 190-140 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, both the sounds impinging on the target and the echoes stimulating the auditory system have relatively flat spectra, with no lowpass filtering due to location. This isolates the spectral ripple caused by target shape to facilitate object classification in flight (Simon et al, 2014;Falk et al, 2011). Bats also receive much stronger reflections from clutter located off to the sides ( (Hartley and Suthers, 1989).…”
Section: −1mentioning
confidence: 99%
“…Detectability of targets at distances of 10-20 m depends on reception of the lowest frequencies that survive over long distances through the air (Holderied et al, 2005;Stilz and Schnitzler, 2012;Surlykke and Kalko, 2008). The object's shape also contributes to the echo spectrum due to reinforcement and cancellation at specific frequencies caused by overlapping reflections from different parts of the object, or 'glints' (Simon et al, 2014;Moss and Zagaeski, 1994;Simmons and Chen, 1989). Interference between glint reflections creates multiple spectral nulls in insect echoes (Fig.…”
Section: −1mentioning
confidence: 99%
See 1 more Smart Citation
“…In a few other events, the acoustic and foraging behaviour of the bats show some similarity to echoic detection of immobile prey by Micronycteris microtis . This recent account, past suggestions of its possibility Weinbeer et al, 2013;Simon et al, 2014) and for other task-specific purposes during substrate foraging , highlights the functional relevance of active echoic strategies in many gleaning bats. Given some earlier work on the neurobiology of N. gouldi , and more recently the functionally specific parallel processing achievable by A. pallidus , this direction of inquiry could reveal specific insight on the functional relevance of acoustic strategies in these Nyctophilus bats.…”
Section: Background and Study Findingsmentioning
confidence: 62%